Isoniazid and Rifampicin Produce Hepatic Fibrosis through an Oxidative Stress-Dependent Mechanism - Ayan Biswas; Suman Santra; Debasree Bishnu; Gopal Krishna Dhali; Abhijit Chowdhury; Amal Santra (International Journal of Hepatology)
Background & Aims. Chronic hepatitis (CH) has emerged as a distinct outcome of drug-induced liver injury (DILI). Combination therapy of Isoniazid (INH) and Rifampicin (RMP) which is widely used for prolonged periods can cause acute hepatotoxicity and has been also incriminated in chronic DILI. We sought evidence of the production of hepatic fibrosis on long-term INH-RMP treatment through experiments in BALB/c mice exposed to INH-RMP. Methods. A combined dose of INH (50 mg) and RMP (100 mg) per kg body weight per day was administered to mice by oral gavage, 6 days a week, for 4 to 24 weeks for the assessment of liver injury, oxidative stress, and development of hepatic fibrosis, including demonstration of changes in key fibrogenesis linked pathways and mediators. Results. Progressive increase in markers of hepatic stellate cell (HSC) activation associated with changes in matrix turnover was observed between 12 and 24 weeks of INH-RMP treatment along with the elevation of liver collagen content and significant periportal fibrosis. These were associated with concurrent apoptosis of the hepatocytes, increase in hepatic cytochrome P450 2E1 (CYP2E1), NADPH oxidase (NOX) activity, and development of hepatic oxidative stress. Conclusions. INH-RMP can activate HSC through generation of NOX-mediated oxidative stress, leading to the development of liver fibrosis.